BANJAR GEN-Z PERSPECTIVE ON THE BAPIDARA TRADITION - Asfa Zahra Maulida; Ihya Hazairin Noor; Salsabella; Qathrun Nada; Annita Nur Rizqia; Pedro Gianthino (Ikatan Dosen Menulis, 2023)
Bapidara is a technique of traditional medicine originating from the Banjar tribe in South Kalimantan, used to treat kapidaraan disease. The Bapidara tradition refers to the medicine of the Dayak Meratus people, which has been influenced by Islam. Bapidara involves the use of turmeric, limewater, and verses of the Qur'an. Kapidaraan is a fever disease believed to be caused by supernatural powers and generally affects children. This research is a qualitative study with a phenomenological design conducted in Tanjung Rema Village, Banjar Regency. Informants consisted of Gen-Z teenagers, Bapidara practitioners, and community representatives. The results show that Gen-Z has varied views towards the Bapidara tradition, some are skeptical, while others try to maintain the tradition and promote it. Bapidara practitioners explained the differences in the processes and ingredients used and highlighted the importance of preserving this tradition through descendants who inherit the knowledge. This research has theoretical and practical value in preserving Banjar Tribe culture and understanding Generation Z's views on the Bapidara tradition. In addition, the results of this study can provide insight into the factors that influence the understanding and appreciation of this tradition, and potentially support efforts to preserve the Bapidara tradition in the modern era.